Improvement of E-Government Service Usability in Developing Countries: Empirical Experiences of Uganda - Mayoka Kituyi, Geoffrey; Anjoga, Humphrey (Journal of Emerging Trends in Computing and Information Sciences, 2013)
Despite several developments in e-Government, governments and citizens in most developing countries ineffectively and inadequately use e-Government services. This study sough to examine the areas in which usability of e-Government services in developing countries can be improved. Both quantitative and qualitative research methods were used to collect and analyze data. A sample of 20 Government ministries under the National Backbone Project directory in Uganda was selected to participate in the study. Findings indicate that functionality, flexibility, cost usability and accessibility are major requirements for improved e-Government service usability in developing countries. In addition, this paper posits that e-Government platforms should take consideration of accessibility, screen design, media use, and consistency, interactivity and content usefulness to the citizens in order to achieve successful usability of e-Government services.
Keywords: E-Government; e-Government services; Service usability; Developing countries; Uganda